JUVENILE GRANULOSA CELL TUMOR IN A 5 YEARS-OLD BULGARIAN GIRL PRESENTING WITH PRECOCIOUS PUBERTY: A CASE REPORT - Diana Hristova; Ivan Kostov; Radko Tocev; Tanya Petkova; Ibryam Ibryam (Journal of IMAB)
Ovarian tumors in children before puberty are rare and usually non-malignant. Granulosa cell tumors are rare sex cord-stromal tumors, accounting for 5% of all ovarian tumors and occur mainly in premenarchal girls and in women younger than 30 years. The diagnosis is based on the presence of precocious puberty, advanced bone age, palpable abdominal mass, nonspecific abdominal pain and abdominal swelling, vaginal discharge. In adolescent, it manifests with signs of menstrual irregularity and virilization. This is a case report of a 5-year-old Bulgarian patient with clinical and paraclinical findings of peripheral precocious puberty who underwent unilateral salpingo-oophorectomy after US and MRI was performed. From the performed imaging studies, Juvenile granulosa cell tumors was suspected. Histological findings confirmed the primary diagnosis – Granulosa cell tumor of juvenile type and TMN staging was: pT1a. It was decided not to perform adjuvant chemotherapy in view of the stage of the tumor process according to existing algorithms and the decision of the oncology committee. Generally, the prognosis is good. The most important prognostic factor associated with a higher risk of relapse is the stage of disease. Prolonged surveillance is essential in the described case because the disease tends to recur years after the initial diagnosis.